2022
DOI: 10.1001/jamasurg.2022.2749
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic vs Open Distal Gastrectomy for Locally Advanced Gastric Cancer

Abstract: IMPORTANCEThe long-term safety of laparoscopic distal gastrectomy for locally advanced gastric cancer (AGC) remains uncertain given the lack of 5-year follow-up results.OBJECTIVE To compare the 5-year follow-up results in patients with clinically AGC enrolled in the Korean Laparoendoscopic Gastrointestinal Surgery Study (KLASS)-02 randomized clinical trial who underwent laparoscopic or open distal gastrectomy. DESIGN, SETTING, AND PARTICIPANTSThe KLASS-02, a multicenter randomized clinical trial, showed that l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Short-term benefits include reduced postoperative morbidity and earlier recovery, which usually also translate into shorter hospital stay [11][12][13][14]. Long-term outcomes have also been reported in recent years, showing that laparoscopic and open surgery are equivalent in terms of oncological safety and survival [15,16]. The issue is that for the most part, the body of evidence on gastric cancer surgery is generated in high-incidence East Asian countries.…”
Section: Introductionmentioning
confidence: 99%
“…Short-term benefits include reduced postoperative morbidity and earlier recovery, which usually also translate into shorter hospital stay [11][12][13][14]. Long-term outcomes have also been reported in recent years, showing that laparoscopic and open surgery are equivalent in terms of oncological safety and survival [15,16]. The issue is that for the most part, the body of evidence on gastric cancer surgery is generated in high-incidence East Asian countries.…”
Section: Introductionmentioning
confidence: 99%
“…The KLASS-02 study reported a lower complication rate in the laparoscopic group than in the open group (6.5% vs. 11.0%, P=0.01). The 5-year OS of LDG (88.9%) was not inferior to that of ODG (88.7%, P=0.30) [ 314 315 ] ( Fig. 11 ).…”
Section: Surgical Treatment ( Flowchart 3 ...mentioning
confidence: 97%
“…In Reply We appreciate the interest expressed by Pohekar and Shinde in our article . They raised 3 issues: (1) the survival rates were higher than those in the American Joint Committee on Cancer 8th edition, (2) a high proportion of patients with pathologic stage 1 cancer was included, and (3) adjuvant chemotherapy was given instead of perioperative chemotherapy.…”
mentioning
confidence: 99%